Strategi Pengembangan Usaha melalui Peningkatan Kualitas Produk Ice Coconut Long Black di Titik Temu Coffee Shop, Seminyak, Badung - Natakusumah, Dwiki Firmandiri; Wiranatha, A. A. P. Agung Suryawan; Satriawan, I Ketut (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2019)
This study aims to analyze consumer perceptions of the level of importance and performance of companies related to Ice Coconut Long Black products and to develop appropriate strategies for improving the quality of Ice Coconut Long Black products at Titik Temu Coffee Shop, Seminyak, Badung. This study uses a survey method with the distribution of questionnaires, namely an analysis of the importance and performance of Ice Coconut Long Black products and an analysis of the importance of consumers of Ice Coconut Long Black products and competing products namely Coconut Espresso Martini at Missibu Coffee Shop. These analyze use two methods, namely the Importance Performance Analysis (IPA) method and the Quality Function Deployment (QFD) method. In the analysis of the IPA, there are 3 attributes in the first quadrant of cartesius diagram, which is the top priority. Such product taste, product color and product price. While the value of the total suitability obtained is still below 100%, which is equal to 89,15%, which means that the importance of consumers have not been fulfilled by the performance of the company/product. Whereas QFD produces the priority of increasing product attributes starts from the product’s taste because it gets the highest repair ratio value, while the priority of increasing technical parameters starts from controlling the quality of ice cubes, coconut water and espresso because it gets the highest level of technical importance. Keywords: Importance Performance Analysis, Quality Function Deployment, Ice Coconut Long Black